2021
DOI: 10.5539/mas.v15n3p1
|View full text |Cite
|
Sign up to set email alerts
|

About Clostridium botulinum, Fish and Tilapia

Abstract: Fish and products are considered a food of nutritional quality that constituents a part of the human diet, produced and commercialized worldwide. Tilapia is one of the main fish for aquaculture production destined for human consumption in different presentations: refrigerated, frozen, fillet, cured, canned, among others. Fish, in addition to being a highly nutritious food, is also sensitive to deterioration and contamination along the food chain, being able to be contaminated mainly by microorganisms that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The presence of these bacteria in fish may be due to direct contact with aquatic environments, as well as the ingestion of C. botulinum or spores present in contaminated sediments or feed (16). Studies of marine sediment samples from the Baltic Sea revealed a very high prevalence of C. botulinum type E, up to 100% (32,33).…”
Section: Clostridium Botulinummentioning
confidence: 99%
“…The presence of these bacteria in fish may be due to direct contact with aquatic environments, as well as the ingestion of C. botulinum or spores present in contaminated sediments or feed (16). Studies of marine sediment samples from the Baltic Sea revealed a very high prevalence of C. botulinum type E, up to 100% (32,33).…”
Section: Clostridium Botulinummentioning
confidence: 99%
“…bacteria. The anaerobic conditions of the canning process create a favourable environment for the germination of Clostridium spores, causing their transition into the vegetative form and subsequent toxin production ( 8 , 14 ).…”
Section: Introductionmentioning
confidence: 99%